LATERAL PERCUTANEOUS NEPHROLITHOTOMY IN HORSESHOE KIDNEY: AN ALTERNATIVE APPROACH WITH HIGH SUCCESS RATE - Wahyudi, Yuvi; Pramod, Sawkar Vijay; Safriadi, Ferry (Indonesian Urological Association, 2025)
Objective: This case report was aimed to present a lateral percutaneous nephrolitotomy (PCNL) approach for a patient with horseshoe kidney, few comorbidities, and the outcome of this procedure. Case(s) presentation: A 70 years old obese male came into our hospital with pain in the left flank. Upon CT scan examination, we found that the patient has Horseshoe kidney with left hydronephrosis. The hydronephrosis resulted from obstruction caused by left kidney pelvic stone with a size of 25 x 20 mm. We decided to do lateral PCNL for this case with an excellent result. Discussion: With newer advancements in urology, different minimally invasive treatment modalities are available to manage stone disease in HSKs. PCNL has shown the better result with fewer complications to remove calculi from HSKs and is accepted as a routine treatment of large calculi in HSK, showing a high SFR ranging from 71% to 88%. Lateral percutaneous access of the renal collecting system is safe, as it is gained on the opposite side to where the renal blood vessels enter the kidney. Conclusion: Stone management in patients with horseshoe kidneys is a challenging procedure in endourology, however percutaneous nephrolithotomy is considered a safe and effective treatment option in patients with renal stones in a horseshoe kidney with acceptable result. Keywords: Horseshoe kidney, percutaneous nephrolithotomy, lateral PCNL.